Antithrombotic Therapy Duration after Patent Foramen Ovale Closure for Stroke Prevention: Impact on Long-Term Outcome - Joelle Kefer; Karlien Carbonez; Sophie Pierard; François-Pierre Mouthuy; Andre Peeters; Cedric Hermans; Catherine Lambert; Christophe DeMeester; Thierry Sluysmans; Agnes Pasquet (Journal of Interventional Cardiology)
Background. The optimal duration of antithrombotic therapy (ATT) after patent foramen ovale (PFO) closure remains under debate. This study sought to compare the clinical outcome of patients receiving antithrombotic agents for a short (6 months) versus extended (>6 months) period after the procedure. Methods. This was a retrospective cohort study using a propensity score matching analysis on 259 consecutive patients (131 males, 43 ± 10 years) undergoing PFO closure due to cryptogenic stroke, with complete follow-up (median duration of 10 [4–13] years). The outcome was compared between patients receiving short-term (Group short, N = 88) versus extended ATT (Group long, N = 171). Results. The PFO closure device was successfully implanted in all cases, with 3% of minor complications. After propensity score matching, there were no differences between Groups short and long in the rate of stroke (0.3 vs. 0.4% patient-year, p=1.00), bleeding (2 vs. 2% patient-year, p=0.17), and device thrombosis (0.3 vs. 0.1% patient-year; p=0.60). Univariate analysis showed that short-term ATT was not associated with an increased risk of recurrent stroke (HR: 1.271 [95% CI: 0.247–6.551], p=0.775) or prosthesis thrombus (HR: 0.50 [95% CI: 0.070–3.548], p=0.72). Kaplan–Meier analysis revealed similar overall survival in Group short and long (100 vs. 99 ± 1%, respectively; p=0.25). Conclusions. Short-term (6 months) ATT after PFO closure did not impair the clinical outcome, with a preserved low rate of recurrent stroke (0.3% patient-year) and device thrombosis (0.2% patient-year) at 10-year follow-up.